The impact of health information needs' satisfaction of hypertensive patients on their clinical outcomes. Issue 1 (11th December 2020) - Kostagiolas, Petros; Milkas, Anastasios; Kourouthanassis, Panos; Dimitriadis, Kyriakos; Tsioufis, Konstantinos; Tousoulis, Dimitrios; Niakas, Dimitrios
Abstract : Purpose: The ultimate aim of this study is to investigate how health information needs' satisfaction actually makes a difference to the patients' management of a chronic clinical condition. The literature falls short of providing evidence on the interaction between patients' health information seeking behaviour and the successful management of a clinical condition. On the other hand, patient education and good information seeking practices are deemed necessary for hypertension management daily decisions. Design/methodology/approach: A specially designed questionnaire study was developed: The survey design was informed by the information seeking behaviour model of Wilson for studying hypertension patients' information needs, information resources and obstacles patients face while seeking hypertension-related information. Moreover, clinical information was collected in order to make associations and inference on the impact of information seeking on patients' clinical outcomes. Findings: The study included 111 patients submitted to the outpatient hypertension clinic of a university hospital in Athens for a 24-h ambulatory blood pressure measurement (ABPM). The analysis showed that those reporting higher satisfaction level of their information needs achieved lower values in ABPM (ABPM<130/80mmHg, p  = 0.049). Stepwise the logistic regression analysis revealed three independent factors to predict the possibility of being optimally treated (ABPM<130/80mmHg). Dipping status (OR: 14.052, 95% CI: 4.229–46.688, p  = 0.0001) patients with high satisfaction level of their disease (OR: 13.450, 95% CI: 1.364–132.627, p  = 0.026) and interpersonal relationships were used as the main source of information (OR: 1.762, 95% CI: 1.024–3.031, p  = 0.41). Originality/value: Hypertensive patients with high satisfaction level of information achieve better disease control. Among different sources of information, interpersonal relationships emerge as the most appropriate factor for patients' disease control.